Numerical analysis of oil combustion in a small combustion device - Zadravec, Matej; Rajh, Boštjan; Samec, Niko; Hriberšek, Matjaž (Anali PAZU, 2022)
This paper focuses on the numerical analysis of the combustion of the liquid fuel Extra Light Fuel Oil (ELFO) in a small combustion device. The calculation was performed by ANSYS CFX computer code for experimental optimal air-fuel ratio (λopt) and the middle power of the oil burner Weishaupt WL5/1-A (37 kW). The goal of the numerical analysis was to establish, whether the experimentally determined λopt ensured the conditions for a complete combustion in each point of the combustion chamber. The comparison of numerical results and measured values confirm the suitability of the chosen numerical model.